EMPLOYEE ENGAGEMENT PADA PT PJB - Fitriani, Arbania (Jurnal Psikologi : Media Ilmiah Psikologi, 2019)
AbstractThis study aims to get an overview of Employee Engagement at PT PJB in Surabaya, East Java,Indonesia so that the information in this study can be used by the Directors and Management to develop a work culture that can encourage employee productivity. This research used non- experimental quantitative / EPF methods. The subjects of this study were employees of PT PJB who were permanent employees, not in work assignments, and had worked at PT PJB for at least 1 year. There are 10 Engagement indicators measured in the study , Cultural Reputation (RB), Career Management (MKa), Performance Management (Mki), Award Recognition (R), Work Environment (LK), Compensation Benefit (KB), Leadership (K), Team Cooperation (KT), Employee Development (PK), and Work Value (NK). The scale used is Likert scale using two scales, namely the Satisfaction Scale and the Urgency Scale where the sum of the distribution of satisfaction scales and urgencies will be defined as the engagement index. The results of frequency distribution showed satisfaction and Engagament presentation indices in PT PJB at 77.2% and 82.5%. This shows that employees at PT PJB already feel satisfied and interested in the organization where the factors that are considered to be the greatest percentage in encouraging satisfaction and engagement are factors of team collaboration. Based on multiple regression test, shows ttest > t table and p < 0,05 which means model and variables are valid. From the Regression model IKK = 74,690 + 0,011 RB + 0,060 MKa – 0,023MKi + 0,013 RP + 0,001 LK - 0,013 KB + 0,0001 KP + 0,046 KT - 0,007 PK + 0,011 NK, can be concluded that every 1% increase in satisfaction on the Career Management indicator will increase engagement level by 0.06% and every 1% increase in satisfaction on the Team Cooperation indicator will increase the engagement rate by 0.046%. Keywords : Engagement, Employee Engagement AbstrakPenelitian ini bertujuan untuk mendapatkan gambaran mengenai Employee Engagement pada PT PJBdi Surabaya Jawa Timur Indonesia agar kemudian informasi dalam penelitian ini dapat digunakan oleh pihak Direksi dan Manajemen untuk mengembangkan budaya kerja yang dapat mendorong produktivitas karyawan. Penelitian dilakukan dengan metode kuantitatif non eksperimental/EPF. Subjek penelitian ini adalah karyawan PT PJB yang berstatus pegawai tetap, tidak dalam tugas karya, dan telah bekerja di PT PJB minimal selama 1 tahun. Terdapat 10 indikator Engegament yang diukur dalam penelitian yakni Reputasi Budaya (RB), Manajemen Karir (MKa), Manajemen Kinerja (Mki), Rekognisi Penghargaan (R), Lingkungan Kerja (LK), Kompensasi Benefit (KB), Kepemimpinan (K), Kerjasama Tim (KT), Pengembangan Karyawan (PK), dan Nilai Kerja (NK). Skala yang digunakan adalah skala Likert dengan menggunakan dua skala yakni Skala Kepuasan dan Skala Kepentingan dimana penjumlahan distribusi skor skala kepuasan dan kepentingan akan didefinisikan sebagai indeks engagement. Hasil distribusi frekuensi menunjukkan indeks presentasi Kepuasan dan Engagament pada PT PJB masing-masing sebesar 77.2 % dan 82.5 %. Organisasi dimana faktor yang dianggap paling besar persentasinya dalam mendorong tingkat kepuasan dan engagement adalah faktor kerjasama tim masing-masing untuk skala kepuasan adalah sebesar 85 % dan skala engagement adalah sebesar 82 %. Hasil uji regresi serentak menunjukkan model dan parameter signifikan denganmodel sebagai berikut IKK = 74,690 + 0,011 RB + 0,060 MKa – 0,023 MKi + 0,013 RP + 0,001 LK -0,013 KB + 0,0001 KP + 0,046 KT - 0,007 PK + 0,011 NK. Dapat disimpulkan bahwa setiap 1%kenaikan kepuasan pada indikator Manajemen Karir akan menambah tingkat engagement sebesar0,06% dan setiap 1% kenaikan kepuasan pada indikator Kerjasama Tim akan menambah tingkatengagement sebesar 0,046%. Kata kunci: Engagement, Employee Engagement